Interprofessional Collaborative Strategies for Optimizing Antibiotic Adherence in Diabetic Foot Infections: A Review Evaluation of Nurse-led, Preventive Medicine Specialists-Led, Pharmacist-led, and Physician-Guided Interventions - Algethami, Abdulmajid Ghowaizi; Melybari, Mohammed Meyassr; Althomali, Naif Musallam Jaber; Alwuthaynani, Safar Mesfer Mohammed; Alharbi, Turki Abdulkarim; Zarban, Yahya Hassan; Asiri, Arwa Saeed; Alghitran, Abdulrahman A.; Dighriri, Ibrahim Mohammed; Alqahtani, Dhafer Ghannam; Alqahtani, Mesfer Abdullah; Alqahtani, Bader Abdullah; et al. (Journal of Ecohumanism, 2024)
Infections of diabetic feet (DFI) comprise a significant healthcare issue where poor adherence to antibiotics results in elevated morbidity, mortality, and healthcare costs. This review discusses inter-professional collaborative approaches for optimizing antibiotic adherence to DFI management. This paper examines the specific but collaborative roles of nurse-led interventions, preventive medicine specialist-led interventions, pharmacist-led interventions, physician-guided interventions, and contributions from medical device specialists. A combination of nurse-led interventions with structured educational programs and telehealth support reduced hospital readmissions by up to 30%. High-risk patients were detected at 40% before traditional methods through risk stratification programs developed by preventive medicine specialists. Simplified regimens and digital tracking tools enable pharmacists to lead interventions with a 25% increase in adherence rates. Physician-guided clinical decision-making helps customize treatment, reducing treatment complications by 35%. The technological solutions of medical device experts, such as wound monitoring and offloading devices, increase wound healing times by 45% when combined with antibiotic therapy. Implementation challenges include financial constraints, logistical barriers, and cultural competence requirements. Evidence shows that appropriately coordinated interprofessional teamwork increases the likelihood of better patient outcomes and reduces DFI-related healthcare expenses by up to 50%. Future studies must identify the best mix of interprofessional interventions and assess their cost-effectiveness. The findings highlight the critical role of established collaborative frameworks, technological integration, and policy reforms in supporting comprehensive DFI management.